Aberrant hippocampal mossy fibers in temporal lobe epilepsy target excitatory and inhibitory neurons. (28th August 2021) - Puhahn‐Schmeiser, Barbara; Leicht, Kathrin; Gessler, Florian; Freiman, Thomas M.
Summary: Objective: The pathoanatomical correlate of temporal lobe epilepsy is hippocampal sclerosis, characterized by selective neuronal death of mossy cells in the hilus and of pyramidal cells in cornu ammonis 1. Although granule cells survive, they lose mossy cells as a target and redirect their axons (mossy fibers) backward into the molecular cell layer. It has been assumed that this process results in excitatory circuits. We therefore examined whether sprouted mossy fibers form synaptic connection not only with excitatory granule cells but also with inhibitory interneurons, such as basket cells. Methods: Resected hippocampal specimens of patients with hippocampal sclerosis were compared to controls of patients with extrahippocampal lesions with only mild sclerosis. Mossy fibers were traced with Neurobiotin or labeled against synaptoporin; inhibitory interneurons were labeled against parvalbumin. Synapses were examined with electron microscopy, labeled with γ‐aminobutyric acid immunogold. Results: Sprouted mossy fibers of epileptic hippocampi innervate not only excitatory granule cells but also inhibitory parvalbuminergic interneurons. Despite neuronal death in hippocampal sclerosis, the axonal plexus of inhibitory parvalbuminergic interneurons surrounding the granule cells is preserved. Connections of sprouted mossy fibers and inhibitory axon terminals were quantified, showing that the number of inhibitory axon terminals significantly exceeds the number of sprouted excitatory mossy fiber terminals (.03 boutons/µm vs. .11 boutons/µm; p < .001). Significance: Although no definite conclusions regarding the function of our findings may be derived from this anatomical study, the observed aberrant connectivity might lead to an increased inhibition and synchronization of granule cells, because the preserved inhibitory interneurons show an additional innervation through sprouted mossy fibers. This might result in the instability of a previously balanced network.